Advances in Lubricated Bearings - Schwarze, Hubert; Hagemann, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint features 12 research articles that contribute to the research on lubricated bearings. The articles focus on the latest steps in understanding bearing operating behavior, its interaction with lubricants, and its role as a component in the drive train. In addition to the description of novel modeling approaches, a variety of experimental data are presented to provide interesting identification results as well as validation data for the research and engineering community.